Do we need human capital heterogeneity for energy efficiency and innovativeness? Insights from European catching-up territories. (June 2023) - Prokop, Viktor; Gerstlberger, Wolfgang; Zapletal, David; Gyamfi, Solomon
Abstract: This study brings a new perspective on the energy efficiency issue within the "catching-up territory" of Southern, Baltic, and Eastern European countries, where such analyses are missing. We create an original theory mix, combining theories of human capital, natural resource-based view, gender socialization, and upper echelons, to address three important research gaps: (i) the missing link regarding the effects of firm-specific human capital on energy efficiency; (ii) the interrelationship between energy efficiency and firms' innovativeness; and (iii) nonlinear relationships between firm-specific human capital, energy efficiency, and innovativeness. Moreover, we test whether energy efficiency has a mediating role within firms' innovation processes. Our results confirm the key role experiences and skills play in energy efficiency and surprisingly refute the importance of gender diversity in this case. We also confirm the importance of environmental behaviour for innovativeness and reveal the mediating role of energy efficiency for process innovations. Finally, we propose several important implications for managers and policy makers. Highlights: The key role of experiences and skills in energy efficiency. Rejection of the importance of gender diversity for energy efficiency. Firms' environmental behaviour triggers innovativeness. The mediating role of energy efficiency for process innovations. Nonlinear relationships revealed.